2021
DOI: 10.1159/000513505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Dose and Detraining Duration on Mobility at Late Midlife: A Randomized Clinical Trial

Abstract: Background: Office workers near retirement tend to be sedentary and can be prone to mobility limitations and diseases. We examined the dose effects of exergaming volume and duration of detraining on motor and cognitive function in office workers at late midlife to reduce sedentariness and mobility limitations. Methods: In an assessor-blinded randomized trial, 160 workers aged 55–65 years performed physically active video games in a nonimmersive form of virtual reality (exergaming) in small, supervised groups f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…The improvements observed in FC were similar to other studies [2,[35][36][37]. Boukabous et al [9] reported that VO2 peak improved after 2-4 weeks of exercise and cardiorespiratory fitness improved after 8 weeks [10].…”
Section: Discussionsupporting
confidence: 84%
“…The improvements observed in FC were similar to other studies [2,[35][36][37]. Boukabous et al [9] reported that VO2 peak improved after 2-4 weeks of exercise and cardiorespiratory fitness improved after 8 weeks [10].…”
Section: Discussionsupporting
confidence: 84%
“…The blood pressure in our study did not reach normative values with nine months of METP, which may indicate that older women with hypertension may need a longer period of exercise to achieve these values. The FC improvements observed were similar to those of Hortobágyi et al [22] and Marcos-Pardo et al [23]. After 8 months of METP, Blasco-Lafarga et al [24] reported improvements in lower body strength (20.23%), agility (22.32%), and aerobic capacity (14.54%), and Leitão et al [10] observed a 11.06% improvement in aerobic capacity after 9 months of MEP, both in normotensive older women.…”
Section: Discussionsupporting
confidence: 80%
“…Compared to people who forego muscle strengthening activities, people who participate in regular strengthening activities reduce their risk of developing functional limitations by nearly 40% compared to those who do not over the course of 25 years [ 36 ]. Even with short term reductions in strengthening habits, detraining effects have been shown to decrease and decreases in mobility, strength, balance, and even executive function in just 1–4 months of detraining [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%